Fuzzy‐based frequency security evaluation of wind‐integrated power systems - Joachim Steinkohl (Wiley, 2021)
Abstract The transition to renewable energy‐based power systems is fast progressing. One of the main challenges in keeping a power system with high operational reliability is to maintain the system frequency. As synchronous generator units are being replaced with power‐electronic converters, the rotating mass and the system inertia are decreasing. Virtual synchronous machine (VSM) control is a modern control technique that aims to compensate for the reduction in inertia. The usage of power electronic‐based converter units equipped with VSM control has to be managed and scheduled by system operators. An assessment of the operational frequency reliability is used to evaluate different service usages. A method is proposed that allows the comparison of different frequency management strategies. The proposed method uses fuzzy logic to evaluate the system risk for abnormal frequency and the system effort in the form of frequency control usage. This allows to quickly compare different frequency management strategies whilst keeping in mind many different reliability indices. The proposed method is validated with a modified IEEE Reliability Test System with integrated wind power capacity.